Effects of Maternal Nightshift Work on Evening Energy Intake, Diet Quality and Meal Timing in the Family: An Observational Study - Alan Flanagan; Elizabeth Lowson; Bruce A. Griffin; Debra J. Skene (MDPI AG, 2021)
The percentage of women working regular nightshift work has increased in the past decade. While nightshift work has the potential to exert adverse effects on dietary habits, little is known about the impact of a parent working nightshifts on dietary habits in the family. We analysed energy intake, meal timing, and diet quality among dependent children and male partners of 20 female UK National Health Service (NHS) nurses working rotational nightshifts. Comparing nightshift against non-nightshift conditions, we hypothesised that maternal nightshift work would affect the evening energy intake, diet quality and time of eating of dependent children and adult partners. Primary outcomes were absolute energy intake and the proportion of daily energy intake consumed in the evening (16:00-23:59 h). Our results show that in pre-teen children aged 8-12 years (n = 13, mean ± SD, 9.9 ± 1.6 yrs; 9 males), the proportion of total daily energy intake consumed during periods of nightshift work was significantly greater compared to periods of non-nightshifts (45.7% ± 8.8% vs. 39.7% ± 7.0%, mean ± SD, p = 0.012). There was no effect of nightshift work on dietary habits in teenage children or partners. The finding of a greater proportion of daily energy consumed in the evening period in pre-teen children is noteworthy, as it suggests that pre-teen children more dependent than older teenage children may be more vulnerable to disruptions to dietary patterns associated with maternal nightshift work.